2021 ESC Guidelines on cardiac pacing and cardiac resynchronization therapy - article Editorial (Российский кардиологический журнал, 2022)
Developed by the Task Force on cardiac pacing and cardiac resynchronization therapy of the European Society of Cardiology (ESC).With the special contribution of the European Heart Rhythm Association (EHRA).